Oxidized Carbon Materials as Hole Transport Layers for High‐Performance Organic Photovoltaics. Issue 4 (21st February 2023) - Han, Nara; Lee, Minwoo; Moon, Yina; Yang, Dongseong; Kim, Dong-Yu
Abstract : Flexible Organic Photovoltaics In article number 2200908, Dong‐Yu Kim and co‐workers introduced an oxidized carbon soot (OCS)‐based hole‐transporting layer to improve charge transport without charge recombination, finally enhancing the device performance up to 15.04%. Due to the functionalization of OCS with octadecylamine, the largesized and flexible organic photovoltaics prepared by blade coating exhibited high storage stability (71% retention) and mechanical stability (78% retention).